Odpowiedzi

2010-01-27T22:03:43+01:00
X+2y=-2
2x-y=1

x=-2-2y
2(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y=1+4 / :(-5)

x=-2-2y
y=-1

x=-2-2(-1)
y=-1

x=-2
y=-1


b)x+4y=-2
3x-8y=10

x=-2-4y
3(-2-4y)=10

x=-2-4y
-6-12y=10

x=-2-4y
-12y=16 / : (-12)

x=-2-4y
y= -1,33

x=-2-4(-1,33)
y= -1,33

x=7
y=-1,33

c)x-2y=3
-2x+y=0
Najlepsza Odpowiedź!
  • Fao
  • Rozwiązujący
2010-01-27T22:10:05+01:00
A) x+2y=-2 / -2y
2x-y=1

x= -2-2y
2×(-2-2y) - y = 1

x =-2 -2y
-4-4y -y =1/+4

x=-2 -2y
-5y=5 / :(-5)

x=-2 -2y
y=-5

x= -2 -2×(-5)
y=-5

x=-12
y=-5

b) x+4y=-2 / -4y
3x-8y=10

x=-2 - 4y
3×(-2 - 4y) - 8y = 10

x=-2 - 4y
-6 - 12y - 8y = 10

x= -2 - 4y
-20y = 16 /:(-20)

x= -2 - 4y
y = -0,8

x= -2 -4×(-0,8)
y=-0,8

x= 1,2
y = -0,8

c) x-2y=3 /+ 2y
-2x+y=0

x=3 + 2y
-2×(3+2y)+y = 0

x=3 + 2y
-6 -4y +y = 0

x=3 + 2y
-3y = 6

x= 3 + 2y
y = -2

x= 3 + 2×(-2)
y = -2

x= -1
y = -2

d) 2x+y=9 / -2x
5x-4y=3

y=9 - 2x
5x - 4×(9 - 2x) = 3

y= 9-2x
5x-36+8x = 3

y = 9-2x
13x = 39

x= 3
y=9 - 2×3

x=3
y=3

e) 3x-2y=5
2x-y=4 / -2x

3x-2y =5
-y=4-2x

3x-2y=5
y=-4+2x

3x-2×(-4+2x)=5
y=-4+2x

3x+8-4x=5
y=-4+2x

-x=-3
y=-4+2x

x=3
y=-4+2×3

x=3
y=2